AN ANALYTICAL APPROACH ON THE BUCKLING ANALYSIS OF CIRCULAR, SOLID AND ANNULAR FUNCTIONALLY GRADED THIN PLATESGRADED THIN - Koohkan, H.; Kimiaeifar, A.; Mansourabadi, A.; Vaghefi, R. (Journal of Mechanical Engineering, 2010)
In this paper, the buckling analysis of circular, solid and annular functionally graded thin plates under uniform radial compression loads is studied. The material properties through the thickness are assumed to be power functions of the thickness. Moreover, the stability equations based on the classical plate theory (CPT), are derived by using the Hamilton’s principle. The obtained coupled-PDEs are difficult to be used for evaluation of the buckling loads of annular plates with various boundary conditions. To resolve this difficulty, a coordinate transformation from the middle plane to a new position is done and as consequence the equations are decoupled. By using the forgoing equations, the buckling loads are determined. The procedure is done for both circular and annular FGM plates of various boundary conditions under uniform radial loads on the edges and the results are validated with one of references. Key Words: Buckling analysis; solid plate; annular plate; functionally graded materials. DOI: 10.3329/jme.v41i1.5357 Journal of Mechanical Engineering, Vol. ME 41, No. 1, June 2010 7-14